2016
DOI: 10.1039/c6ra13447e
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a micro-nanostructured superhydrophobic aluminum surface with excellent corrosion resistance and anti-icing performance

Abstract: Synergy is the key to realizing superhydrophobicity. The as-prepared superhydrophobic Al surface possesses both excellent corrosion resistance and anti-icing performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 86 publications
1
20
0
Order By: Relevance
“…The value of |Z| 0.01 Hz of SLIPS was 10 7 U cm 2 , which was increased by two orders in comparison with the superhydrophobic surface. Similar to other reports, [42][43][44] the values of |Z| in the high-frequency range were evidently different between these four samples. The highfrequency limit of the Bode plots is supposed to represent the electrolyte resistance; the variation at 10 5 Hz was due to the air layer between the superhydrophobic interface and the solution, which made the electrolyte resistance for the superhydrophobic-coated Mg alloy larger than that for the untreated alloy.…”
supporting
confidence: 78%
“…The value of |Z| 0.01 Hz of SLIPS was 10 7 U cm 2 , which was increased by two orders in comparison with the superhydrophobic surface. Similar to other reports, [42][43][44] the values of |Z| in the high-frequency range were evidently different between these four samples. The highfrequency limit of the Bode plots is supposed to represent the electrolyte resistance; the variation at 10 5 Hz was due to the air layer between the superhydrophobic interface and the solution, which made the electrolyte resistance for the superhydrophobic-coated Mg alloy larger than that for the untreated alloy.…”
supporting
confidence: 78%
“…Some reports suggest that surface hydrophobicity can be applied to design the icephobic coatings due to the capability of water repellency and freezing delay [4,5]. Zheng et al fabricated superhydrophobic aluminum surface with hierarchical micro/nano structure by anodization method which had a water contact angle (WCA) of 156°, exhibiting a delay in ice formation and low ice adhesion strength of 40 KPa [6]. Wang et al reported that superhydrophobic steel surface prepared by chemical etching process demonstrated excellent anti-icing properties [7].…”
Section: Introductionmentioning
confidence: 99%
“…For example, via hydrochloric acid etching and potassium permanganate passivation, Li et al constructed micro/nano-scale terrace-like hierarchical structures on 6061 Al alloy surfaces [22]. Through anodization, a hierarchical micro-nanostructure was successfully fabricated on Al substrate by Zheng et al [23].…”
Section: Introductionmentioning
confidence: 99%